An Experimental Investigation of Strength and Thermal Analysis on Mortar with Micro and Nano Flyash - Mohana, Dr. R.; Anitha, A. (International Journal of Scientific Research in Civil Engineering, 2017)
This works aims to study the effect of partial substitution of ordinary Portland cement (OPC) by micro flyash and Nano flyash on the mechanical properties of mortar is investigated. The mechanical properties and thermal analysis of mortar were studied with the combination of micro flyash and nano flyash. A total number of 102 mortar cubes were cast in 70.6mm x 70.6mm, were crushed including the trail experiment. It was calculated with the particular water cement ratio of 0.38. The phase composition of the hydration products was investigated using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), and Energy-Dispersive X-ray Spectroscopy (EDX) were taken to study the morphological and mineralogical composition of the material. The compressive strength of concrete generally increases with increase in the fineness so as to obtain a reduction in porosity. The addition of small closely spaced and uniformly dispersed materials to mortar would substantially improve its mechanical and fire-resistant properties. To increase the fineness of flyash it is converted to nano particles by using ball mill apparatus. Nano flyash acts as a filler agent and it improves the pore structure. From the results, at 600?C flyash and nano flyash combination resist the heat and  reduction in mass  were observed.
Keywords: Flyash; Nano Flyash; Compressive Strength; Elevated Temperature